STRATEGI KOMUNIKASI INSTRUKSIONAL WIDYAISWARA LEMBAGA PENJAMINAN MUTU PENDIDIKAN BENGKULU DALAM PEMBELAJARAN - Titik Fitria Handayani; Henny Afrianti; Syisva Nurwita (UNIVED PRESS, Universitas Dehasen Bengkulu, 2015)
This study aimed to find out thein structional communication strategy of Widyaiswara Education Quality Assurance Agency Bengkulu in learning, includesthe pre-Instructional strategies, the implementationof Instructional strategies, and the results and evaluation of in structional communication strategy. Thisresearchis aqualitative descriptive study. Datawere collected through observation, interviews and documentation. Data analysis was performed with Miles and Huberman(1984) data analysis techniques, namely: data collection, data reduction, data display, and drawing and verification conclution. The results showed: 1) In Pre-Instructional phase, Widyaiswara’sBengkuludo: preparationto implement thetrainingas indicated bya letter of assignmentand directionofthe management, arrange the Learning Implementation Plan(RPP) and Learning Syllabus, develop strategieswill be run in training, studying the entering behaviorand the prior needs oftraining participants during the training. In Instructionalphase the stepsare: determiningthe formulation of the instructional objectivesof education and training, paid attention tothe validity and relevance ofthe material to be delivered to training participants, useda variety of learningmediain the learning process, adapted the medium usedto learning objectives, useda variety of methodsin the learning process, established the source/teaching materialsin accordance withthe needs of training participants, determined appropriate time and appropriate objectives to achieve, encouraged the training participants to actively involve in the learning process. At the stage of evaluation, the steps are: evaluation oftrainingparticipantsin the form of assessmentat the end and assessment during the training through thetest questions.